Penerapan Model Student Teams Achievement Division dengan Utaku untuk Meningkatkan Aktivitas Siswa - Ulfa, Zevi Ismiatul; Ismaya, Erik Aditia; Fardhani, Much Arsyad (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Studentâ€™ activities play an important role in classroom learning activities. Student activities also affect student learning achievement, if the child is active then the possibility of achievement is also good. Unfortunately, Â not all students are active in learning activities. The problem of low student activity occurs at State Elementary School 2 of Medini. The lack of students who ask questions or express opinions showed the activities of students were classified as low. This problem may disturb learning process and can affect student achievement. The purpose of this study is to describe the improvement in student activity through the Student Teams Achievement Division model assisted by Utaku media. The research method used is classroom action research (CAR). The subjects of the study were the fourth grade students of State Elementary School 2 of Medini. The instrument used was a student activity observation sheet. The data analysis technique used is qualitative data analysis technique. The results showed an increase on studentsâ€™ learning activities in the first cycle obtained an average value of 74 and in the second cycle increased to 85. Based on the results of CAR conducted in forth grade of State Elementary School 2 of Medini it can be concluded that the use of the STAD model assisted by Utaku media can increase student activity.